Effects of redox potential on chalcopyrite leaching: An overview. (1st October 2021) - Tian, Zuyuan; Li, Haodong; Wei, Qian; Qin, Wenqing; Yang, Congren
Abstract: Chalcopyrite is a prime, plentiful and widely distributed form of copper-bearing mineral. Compared with the traditional pyrometallurgy process, biohydrometallurgy has environmental and economic advantages, and is thus considered to be a promising mineral-processing technology. However, the dissolution kinetics of chalcopyrite in hydrometallurgy are low due to its high lattice energy. Redox potential has a significant role as chalcopyrite dissolves, and the possibility of controlling redox potential to promote chalcopyrite leaching cannot be ignored. In this article, the impact of redox potential on chemical leaching and bioleaching of chalcopyrite, reported in previous publications, are summarized. The effects of ferrous ions, ferric ions and copper ions in chalcopyrite leaching system are discussed, and the leaching behavior of chalcopyrite is explained by the band theory.